The Terrible Two - Barnett, Mac; John, Jory; Cornell, Kevin (New York : Amulet Books, 2015)
When master prankster Miles Murphy moves to sleepy Yawnee Valley, he challenges the local mystery prankster in an epic battle of tricks, but soon the two join forces to pull off the biggest prank ever seen.
Keywords: Practical jokes -- Juvenile fiction; Tricks -- Juvenile fiction; Schools -- Juvenile fiction; Moving, Household -- Juvenile fiction; Practical jokes -- Fiction; Tricks -- Fiction; Schools -- Fiction; Moving, Household -- Fiction; Humorous Stories; JUVENILE FICTION / Humorous Stories; JUVENILE FICTION / Readers / Chapter Books; JUVENILE FICTION / General